Environmental Sustainability Research and Future Directions for Events and Facilities: An Assessment of the Field - Brian McCullough; Anne Dietrich; Rafael Rocha; Yongjoon Bae (Journal of Applied Sports Management, 2023)
Environmental sustainability among sport facilities and events is the focus of this piece. The authors focus on three areas: (1) the environmental impacts of sport facilities and events, (2) the progress that can be made through strategic initiatives, and (3) how these entities engage fans and the surrounding communities to be more environmentally sustainable. The authors stress how these three aspects must be considered in tandem rather than in isolation as ways to advance the environmental sustainability movement among sport facilities and events.
Keywords: Facility Design; Operation Management; Sport Facilities; Sustainability